Management of pulmonary aspergillosis in AIDS: an emerging clinical problem. Issue 9 (September 1994) - Keating, J J; Rogers, T; Petrou, M; Cartledge, J D; Woodrow, D; Nelson, M; Hawkins, D A; Gazzard, B G
Abstract : AIMS--To review the clinical, radiographic, and therapeutic features of 11 cases of respiratory Aspergillus infection in patients with AIDS. METHODS--All induced sputum and bronchoalveolar lavage samples obtained from HIV seropositive patients between January 1985 and March 1993 were analysed for Aspergillus species. Additionally, where appropriate, bronchial or renal biopsy specimens, or both, were taken before treatment had started. RESULTS--In 11 patients Aspergillus fumigatus was identified in alveolar samples obtained by sputum induction. This was confirmed by bronchoalveolar lavage in eight. Three patients had Aspergillus plaques in the trachea and bronchus, while a fourth patient had an aspergilloma. Risk factors for Aspergillus infection were present in all patients, including corticosteroid treatment in three cases and neutropenia in four, three of whom had received chemotherapy for Kaposi's sarcoma. Four patients had concomitant cytomegalovirus infection. Ten patients had a CD4 count of less than 50 cells/mm3 while one patient had a disseminated T cell lymphoma with a CD4 count of 242 cells/mm3. Of the three patients with samples obtained by sputum induction who did not undergo bronchoscopy, two had a normal chest x ray picture and the third had a right lobar pneumonia complicating an aggressive lymphoma. All three were treated with itraconazole 200 mg twice a day without further investigation. Survival from the time of diagnosis of Aspergillus infection was short: seven patients died within six weeks, although only one death was directly attributed to pulmonary aspergillosis. At six monthly follow up, one patient, who initially had a positive Aspergillus culture from bronchial washings and a normal chest radiograph, developed a renal aspergilloma despite the disappearance of Aspergillus sp from the sputum. CONCLUSION--Pulmonary aspergillosis is an important clinical problem in patients with AIDS with a CD4 count of less than 50 cells/mm. Furthermore, patients with Aspergillus sp in sputum induction or bronchial washings may develop disseminated disease despite adequate treatment of the primary infection.